2018
DOI: 10.1371/journal.pone.0203890
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trends of polypharmacy among HIV-positive and -negative men in the Multicenter AIDS Cohort Study from 2004 to 2016

Abstract: Rates of aging-related comorbidities, which require targeted medications to treat, have been shown to be increased among persons living with HIV compared with uninfected counterparts. Polypharmacy is generally defined as the concurrent use of 5 or more medications. We investigated polypharmacy prevalence for non-HIV medications over a 12-year period among HIV-positive and -negative participants in the Multicenter AIDS Cohort Study. Information regarding non-HIV medication use, HIV status, age, race/ethnicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 25 publications
5
42
0
Order By: Relevance
“…Polypharmacy is also common in the HIV‐positive older adult population . The Swiss HIV cohort study comparing HIV‐positive adults aged ≥50 years with HIV‐positive patients aged <50 years on cART found that older patients were more likely to receive one or more co‐medications compared with younger patients .…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy is also common in the HIV‐positive older adult population . The Swiss HIV cohort study comparing HIV‐positive adults aged ≥50 years with HIV‐positive patients aged <50 years on cART found that older patients were more likely to receive one or more co‐medications compared with younger patients .…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated aging has been associated with HIV-1 infection, and polypharmacy and aging-related comorbidities, such as osteopenia/osteoporosis and increased bone fracture risk, are clinical concerns [1518]. Therefore, evaluation of safety parameters for different age groups is important in studies of new HIV-1 treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…5 Department of Clinical Pharmacology and Pharmacoepidemiology, Heidelberg University Hospital, Heidelberg, Germany. 6 Pulmonology Department, Hospital Universitari Germans Trias i Pujol, Barcelona, Spain.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In addition, HIV patients with PAH or ESRD are frequently affected by other co-morbidities that require specific therapies. These patients often receive many different drugs (polypharmacy), with a potential risk for drug-drug interactions among them [6,7]. Here we report a clinical case involving an HIV-1infected patient with severe PAH and ESRD on hemodialysis who was treated with ambrisentan with the intention to avoid drug interactions between bosentan and cART.…”
Section: Introductionmentioning
confidence: 99%